Ambient PM2.5-bound polycyclic aromatic hydrocarbons (PAHs) in rural Beijing: Unabated with enhanced temporary emission control during the 2014 APEC summit and largely aggravated after the start of wintertime heating. (July 2018) - Yu, Qingqing; Yang, Weiqiang; Zhu, Ming; Gao, Bo; Li, Sheng; Li, Guanghui; Fang, Hua; Zhou, Huaishan; Zhang, Huina; Wu, Zhenfeng; Song, Wei; Tan, Jihua; et al.
Abstract: For human health benefits it is crucial to see if carcinogenic air pollutants like polycyclic aromatic hydrocarbons (PAHs) are reduced accordingly along with the control of the criteria pollutants including fine particles (PM2.5 ). A number of studies documented that enhanced temporary emission control during the 2014 Asia-Pacific Economic Cooperation summit (APEC) in Beijing resulted in substantial drops of observed ambient PM2.5, as well as PAHs, in urban areas of Beijing, yet it is not clear whether PM2.5 -bound PAHs in the rural areas were also lowered during the APEC. Here filter-based PM2.5 samples were collected at a rural site in northeast of Beijing, and analyzed for 25 PAHs before (Oct. 27-Nov. 2, 2014), during (Nov. 3–12, 2014) and after (Nov. 13, 2014–Jan. 14, 2015) the APEC. Observed concentrations of PM2.5, OC and EC during the APEC dropped by about 30%, however, average PM2.5 -bound PAHs and their incremental lifetime cancer risk (ILCR), 25.65 ng/m 3 and 3.2 × 10 −4, remained almost unchanged when compared to that of 25.48 ng/m 3 and 3.5 × 10 −4, respectively, before the APEC. After the APEC with the start of wintertime central heating in urban Beijing on Nov. 15, 2014, average total concentration of PAHs and their ILCR highly elevated and reached 118.25 ng/m 3 and 1.5 × 10 −3, respectively. Source apportioning by positive matrix factorization (PMF) revealed that coal combustion was the largest source that contributed 63.2% (16.1 ng/m 3 ), 78.5% (20.1 ng/m 3 ) and 56.1% (66.3 ng/m 3 ) to the total PAHs before, during and after the APEC, respectively. Uncontrolled residential coal use during the APEC was found to be the reason for unabated levels of PAHs, and the largely aggravated PAHs after the APEC was resulted from increased coal consumption for wintertime residential heating. Our results suggested reducing emission from residential coal combustion is crucial to mitigate carcinogenic PAHs in ambient air, especially in rural areas. Graphical abstract: Image 1 Highlights: Unabated PM2.5 -bound PAHs in the rural with enhanced emission control during the APEC. Largely aggravated PAH pollution after the APEC with the start of wintertime heating. Coal combustion was the major source of PM2.5 -bound PAHs. The contribution of biomass burning to PAHs was reduced during the APEC. Uncontrolled residential coal combustion could explain the undiminished levels of PAHs. Abstract : Ambient levels of PAHs unabated during the 2014 APEC but largely aggravated with wintertime heating due to uncontrolled residential coal burning.